Use of Online Websites as Interactive Learning Media in Moral Creed Lessons - Erna Wahyuni; Rahmi Jumiyah; Wina Asry (International Journal of Educational Narratives, 2024)
Background. The world of the internet is developing very rapidly in this era, in the world of education this technological device is really needed, the use of the internet is closely related to the world of education in the learning process, so that educational institutions have high enthusiasm for developing the use of technology in learning activities. Purpose. The aim of this research is to explain how to use online websites as an interactive learning medium for learning material on moral beliefs. Method. The research method used by researchers is a quantitative method, namely survey model, interviews via the Google Meet application and via Google Form.    Results. The results of this research are to increase students' enthusiasm for learning in the use of learning media and increase students' motivation in learning. Conclusion. The limitations of this research are that the researcher developed an online website platform as a medium and also a learning resource in a district level school and as a tool to motivate and improve learning achievement. students, therefore future researchers can carry out the same research but developed it for several schools across provinces in Indonesia.